Preparation method of titanium diboride reinforced Ni60AA alloy coating on surface of copper plate of continuous casting crystallizer

Through laser directional energy deposition technology and process optimization, a functional gradient coating of titanium diboride enhanced Ni60AA composite material was prepared, which solved the problem of insufficient performance of crystallizer copper plates in high temperature, strong wear and thermal crack resistance, and achieved hardness and resistance to hardness Significant improvement in abrasive and thermal crack resistance.

CN119387516AActive Publication Date: 2025-02-07SHENYANG UNIVERSITY OF TECHNOLOGY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411519094.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The performance of the crystallizer copper plate in high temperature, strong wear and thermal crack resistance is insufficient, resulting in its performance deterioration and ultimate failure under severe operating conditions.

Method used

The functional gradient coating of titanium diboride-enhanced Ni60AA composite material is prepared by using laser directional energy deposition technology and combined with process optimization, so as to achieve metallurgical bonding on the copper plate surface and gradient enhancement of material properties.

Benefits of technology

It significantly improves the hardness, wear resistance and thermal crack resistance of the deposited layer, extends the service life of the crystallizer, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387516A_ABST
    Figure CN119387516A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a titanium diboride reinforced Ni60AA alloy coating on the surface of a copper plate of a continuous casting crystallizer, and belongs to the technical field of laser cladding. The method comprises the following steps that S1, the surface of a base body is pretreated; s2, preheating the base body; s3, preparing a nickel-based cladding layer on the surface of the copper plate as a transition layer; s4, preparing a reinforced deposition layer on the surface of the nickel-based transition layer; and S5, the clad workpiece is machined to the precision and size required by the working condition. The functional gradient coating of the titanium diboride reinforced Ni60AA composite material is designed according to the application requirements of a crystallizer copper plate under challenges of high temperature, high abrasion and thermal cracking resistance. According to the coating, laser directional energy deposition of titanium diboride and nickel-based composite powder on the surface of the copper plate is regulated and controlled, the material performance is gradually enhanced from a substrate to a surface layer, and therefore the hardness, abrasion resistance and hot crack resistance of a deposition layer are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a titanium diboride reinforced Ni60AA alloy coating on the surface of a continuous casting crystallizer copper plate, and belongs to the technical field of laser cladding. Background Art

[0002] The crystallizer is an important equipment in the continuous casting process of steel, and the copper plate is the core component of the crystallizer cooling system. Under harsh service conditions such as high temperature, strong impact, and strong wear, the crystallizer copper plate often suffers from surface wear, high temperature oxidation, and thermal cracking, which leads to its performance deterioration and eventual failure. Therefore, it is necessary to strengthen the surface of the crystallizer copper plate, improve its wear resistance and thermal crack resistance, extend its service life, and reduce production costs.

[0003] Titanium diboride (TiB2) is an excellent modern ceramic material, known for its low density, extremely high hardness (34GPa), high melting point (2900℃) and excellent chemical stability. What is particularly unique is that it also has excellent electrical conductivity that traditional ceramic materials do not have. This feature makes it stand out in a variety of high-tech applications, and therefore has extremely high research and development prospects. Currently, workers are trying to use Ni60AA powder as the base powder and add an appropriate amount of titanium diboride ceramic powder as a reinforcing phase to enhance the bonding strength between the deposited layer and the substrate, and improve the hardness and wear resistance of the deposit.

[0004] Electroplating and thermal spraying are often used to strengthen the copper plate of the crystallizer, but the hardness of the electroplating layer is insufficient. It is easy to soften under high temperature conditions and harsh working environments; voids are easily generated inside the electroplating layer, affecting the strength and wear resistance; the electroplating industry causes environmental pollution, etc. The bonding between the thermal spray coating and the substrate is usually mechanical, and there are internal voids, which affects the overall performance.

[0005] Laser directed energy deposition technology is an additive technology that uses a laser beam to simultaneously melt the metal powder and the matrix material on the surface of the substrate and deposit them on the surface of the substrate. The metal powder is partially melted by the laser beam, and the molten metal powder is deposited on the surface of the substrate to form a deposition layer with excellent performance to achieve surface modification. At the same time, it has the advantages of small heat-affected zone, little thermal damage to the substrate, and metallurgical bonding with the substrate. Compared with traditional surface modification technologies such as electroplating and thermal spraying, the laser directed energy deposition process is easier to automate, and the resulting coating quality is better, which is more in line with the continuous casting process's demand for mold surface strengthening technology.

[0006] It is difficult to eliminate the tiny pores and cracks in the deposited layer by optimizing the process parameters, but preheating the substrate can improve the crack sensitivity of the nickel-based transition deposited layer prepared on the surface of chromium-zirconium-copper alloy. Summary of the invention

[0007] In order to solve the above technical problems, the present invention realizes the surface strengthening of the copper plate of the crystallizer through laser directional energy deposition technology and combines certain process optimization measures, and extends the service life of the crystallizer by preparing a strengthening deposition layer metallurgically combined with the copper plate.

[0008] The present invention aims to solve the problems of low surface hardness and poor wear resistance of a crystallizer copper plate, and provides a titanium diboride reinforced Ni60AA composite material functional gradient coating to achieve crystallizer surface strengthening.

[0009] In order to achieve the purpose of strengthening the surface of the crystallizer, the present invention proposes the following technical solution: a titanium diboride reinforced Ni60AA alloy coating on the surface of a continuous casting crystallizer copper plate and a preparation method thereof, comprising the following steps:

[0010] S1, substrate surface pretreatment;

[0011] S2, substrate preheating;

[0012] S3, preparing a nickel-based cladding layer on the surface of the copper plate as a transition layer;

[0013] S4, preparing a strengthening deposition layer on the surface of the nickel-based transition layer;

[0014] S5, processing the clad workpiece to the required accuracy and size of the working condition;

[0015] In the above step S1, the base material is a Cu-Cr-Zr alloy, and the weight percentages of the components are Cu: 99.25%, Cr: 0.65%, and Zr: 0.1%.

[0016] In the above step S1, the substrate is first polished with sandpaper before processing to remove the oxide film and a large amount of copper rust. Since copper has a low laser absorption rate, after removing the oxide film and copper rust on the surface, the surface is polished and roughened with 60-mesh sandpaper to increase the absorbance, and then the surface of the substrate is cleaned with anhydrous ethanol to ensure a clean and flat surface and reduce experimental errors.

[0017] In the above step S2, the preheating temperature is 400°C.

[0018] In the above step S3, the deposited powder is Ni60AA powder with a particle size of 100-200 meshes.

[0019] In the above step S3, the process parameters suitable for LDED (Laser Directed Energy Deposition) of the nickel-based transition layer on the surface of the crystallizer are laser power 850W, scanning speed 480mm / min, powder feeding rate 0.5r / min, and overlap rate 40%.

[0020] In the above step S4, Ni60AA powder is used as the base powder, 3 wt.% (weight percentage) of titanium diboride ceramic powder is added to form a composite powder, and 0.5% of Y2O3 is added to refine the deposited layer structure.

[0021] In the above step S4, the process parameters for preparing the enhanced deposition layer are: laser power 850 W, scanning speed 480 mm / min, powder feeding rate 0.5 r / min, and overlap rate 40%.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] Aiming at the application requirements of crystallizer copper plates under high temperature, high wear and thermal cracking resistance, the present invention designs a functional gradient coating of titanium diboride reinforced Ni60AA composite material. This coating achieves a gradual enhancement of material properties from the base to the surface by regulating the laser directed energy deposition of titanium diboride and nickel-based composite powder on the surface of the copper plate, thereby significantly improving the hardness, wear resistance and thermal cracking resistance of the deposited layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a process principle diagram for preparing alloy coating using laser cladding equipment in the present invention.

[0025] Figure 2 It is the metallographic structure diagram of the crystallizer copper plate of the present invention.

[0026] Figure 3 A particle diagram of Ni60AA powder used as the transition layer of the present invention.

[0027] Figure 4 This is a metallographic diagram of the cross section of the overlapping deposited layers of the present invention.

[0028] Figure 5 It is a comparison diagram of the preheating simulation and experiment of the present invention.

[0029] Figure 6 This is a microhardness distribution diagram of the deposited layer with different titanium diboride addition amounts of the present invention.

[0030] Figure 7a-7d The three-dimensional wear morphology of the substrate and the reinforced deposited layer with different titanium diboride contents of the present invention is shown in FIG. Figure 7a-7d The upper long strip and the lower arc shape are a whole picture. The upper long strip is used to mark the wear depth. The wear depth mark shows Figure 7a-7d The corresponding wear depth of the arc shape in the lower middle part.

[0031] Figure 8 It is a curve diagram of the friction coefficient of the present invention changing with time.

[0032] Fig. 9This is a cylindrical weight loss graph of the deposit layer with different titanium diboride addition amounts according to the present invention. DETAILED DESCRIPTION

[0033] The technical features and advantages of the present invention are described in detail below in conjunction with the accompanying drawings.

[0034] like Figure 1 As shown, the technology used in the present invention is laser directed energy deposition technology. Laser directed energy deposition equipment is used to prepare the nickel-based coating.

[0035] like Figure 2 As shown, the copper plate of the present invention is a crystallizer copper plate, and the base material is a chromium-zirconium-copper alloy, wherein the weight percentages are Cu: 99.25%, Cr: 0.65%, and Zr: 0.1%.

[0036] like Figure 3 As shown, a nickel-based alloy is selected from the metal powder, which has a linear expansion coefficient closest to that of the copper alloy. The nickel-based alloy can form a good metallurgical bond with the matrix to extend the service life of the crystallizer while also taking into account the economy of use. The deposition powder used is Ni60AA powder with a particle size of 100-200 meshes.

[0037] The relationship between LDED process parameters and the quality and morphology of the deposited layer is very close, so the optimization of process parameters is of inevitable importance to improving the quality and morphology of the deposited layer. Aiming at process optimization, a method for optimizing the LDED process parameters of the nickel-based transition layer on the surface of the crystallizer based on entropy weight-TOPSIS is proposed. The calculation results determine that the combination of 850W laser power, 480mm / min scanning speed and 0.5r / min powder feeding rate is the ideal process parameter for the nickel-based deposition layer on the surface of chromium-zirconium-copper alloy by laser directional energy deposition.

[0038] The width of a single deposition layer is limited, and laser directed energy deposition technology is required to prepare a large area of ​​multiple overlapping deposition layers to meet the use of the crystallizer in actual situations. According to recent research, the present invention selects an overlap rate of 40%.

[0039] like Figure 4 The cross-sectional morphology of the deposited layer shown in the figure indicates that the optimized process parameters can improve the quality of the deposited layer to a certain extent, but some pore cracks cannot be completely eliminated by adjusting the process parameters.

[0040] The present invention explores the crack suppression mechanism of Ni60AA deposited layer by substrate preheating, analyzes the theoretical basis of temperature field, selects Gaussian heat source model, uses JMatPro software to calculate the thermal physical properties of materials at different temperatures, creates and solves the adaptive temperature field model in ANSYS, and combines experiments at different temperatures, preheating simulation and experimental comparison. Figure 5As shown in the figure, it is proved that substrate preheating can reduce both cracks and pores in the deposited layer, and the optimal preheating temperature is 400℃.

[0041] The present invention uses Ni60AA powder as the base powder, adds an appropriate amount of titanium diboride ceramic powder as a reinforcing phase to improve the performance of the deposited layer. And adds 0.5% Y2O3 to the composite powder to refine the deposited layer structure. Figure 6 As shown in the figure, with the increase of titanium diboride addition, the microhardness of the strengthened deposited layer gradually increases, the microhardness of the transition deposited layer is about 651.8HV0.1, and the average microhardness of the strengthened deposited layers with titanium diboride addition of 1%, 2%, and 3% are 729.96HV0.1, 838.94HV0.1, and 1225.3HV0.1, respectively, which are about 1.12 times, 1.29 times, and 1.68 times higher than that of the Ni-based transition layer, and about 5.40 times, 6.21 times, and 9.07 times higher than that of the matrix chromium-zirconium-copper alloy, respectively.

[0042] like Figure 7a-7d The three-dimensional wear morphology of the substrate and the reinforced deposit layer with different titanium diboride contents is shown. Compared with the substrate, the depth and width of the wear scar are significantly improved. This shows that the wear resistance of the reinforced deposit layer with the addition of ceramic reinforcement phase has been improved, and the wear condition has been improved.

[0043] from Figure 8 It can be seen that under the same friction speed and applied load, the friction coefficient of the matrix chromium-zirconium-copper alloy has been rising and finally tends to fluctuate to a stable value. This is because the wear debris generated by the friction and wear experiment at the beginning will cause the friction coefficient to increase continuously. Under the continuous accumulation of wear debris, the friction coefficient increases very quickly; and the friction coefficient change trends of Ni60AA reinforced deposition layers with different titanium diboride contents are roughly the same.

[0044] like Fig. 9 As shown in the figure, after 3600 seconds of reciprocating friction, the wear resistance of the strengthened deposited layer is relatively greatly improved compared with the chromium-zirconium-copper alloy substrate, which proves that the unmelted titanium diboride particles and the newly formed reinforcement phase in the strengthened deposited layer play an anti-wear role and effectively resist the cutting effect of the ceramic on the grinding pair, thereby reducing the wear amount and improving the wear resistance.

[0045] The above description is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent adjustment or innovation made within the technical framework of the present invention and based on the principles and ideas of the present invention shall be deemed to fall within the scope of patent protection of the present invention.

Claims

1. A method for preparing a titanium diboride reinforced Ni60AA alloy coating on the surface of a continuous casting crystallizer copper plate, characterized in that: The following steps are involved: S1: substrate surface pretreatment; S2: substrate preheating; S3: preparing a nickel-based cladding layer on the surface of the copper plate as a transition layer; S4: preparing a strengthened deposition layer on the surface of the nickel-based transition layer; S5: Process the cladding workpiece to the required accuracy and size of the working conditions.

2. The method for preparing the titanium diboride reinforced Ni60AA alloy coating on the surface of the continuous casting crystallizer copper plate according to claim 1, characterized in that: In the step S1, the base material is a Cu-Cr-Zr alloy, and the weight percentages are Cu: 99.25%, Cr: 0.65%, and Zr: 0.1%.

3. The method for preparing the titanium diboride reinforced Ni60AA alloy coating on the surface of the continuous casting crystallizer copper plate according to claim 1 or 2, characterized in that: In the step S1, the failed position of the substrate is derusted and roughened with sandpaper to achieve the surface finish requirement of the crystallizer strengthening based on laser directed energy deposition, and the substrate surface is cleaned with anhydrous ethanol to meet the processing requirements.

4. The method for preparing the titanium diboride reinforced Ni60AA alloy coating on the surface of the continuous casting crystallizer copper plate according to claim 3, characterized in that: In the step S2, the substrate preheating temperature is 400°C to achieve transition layer crack suppression.

5. The method for preparing the titanium diboride reinforced Ni60AA alloy coating on the surface of the continuous casting crystallizer copper plate according to claim 4, characterized in that: The deposition powder used in step S3 is Ni60AA powder with a particle size of 100-200 meshes.

6. The method for preparing the titanium diboride reinforced Ni60AA alloy coating on the surface of the continuous casting crystallizer copper plate according to claim 5, characterized in that: The process parameters suitable for LDED nickel-based transition layer on the surface of the crystallizer in step S3 are laser power of 850 W, scanning speed of 480 mm / min, powder feeding rate of 0.5 r / min, and overlap rate of 40%.

7. The method for preparing the titanium diboride reinforced Ni60AA alloy coating on the surface of the continuous casting crystallizer copper plate according to claim 6, characterized in that: In step S4, Ni60AA powder is used as a base powder, 3 wt.% of titanium diboride ceramic powder is added to form a composite powder, and 0.5% of Y2O3 is added to refine the deposited layer structure.

8. The method for preparing the titanium diboride reinforced Ni60AA alloy coating on the surface of the continuous casting crystallizer copper plate according to claim 7, characterized in that: The process parameters for preparing the enhanced deposition layer in step S4 are: laser power 850 W, scanning speed 480 mm / min, powder feeding rate 0.5 r / min, and overlap rate 40%.

Citation Information

Patent Citations

  • Laser cladding in-situ synthesized boride ceramic coating and preparation method thereof

    CN102864453A

  • Material for TA15 titanium alloy surface laser cladding and laser cladding method

    CN103628056A

  • High-temperature-resistant composite coating material on surface of titanium alloy based on laser cladding

    CN110923707A

  • Rare earth-containing titanium alloy surface self-lubricating wear-resistant coating and preparation method thereof

    CN111575704A

  • High-entropy alloy-based gradient composite ceramic wear-resistant coating and high-speed laser cladding in-situ preparation method thereof

    CN114990542A